THE ROLE OF QUALITY OF ACCOUNTING SYSTEMS AND INFORMATION IN OPTIMIZING OPD PERFORMANCE THROUGH DECISION MAKING (SURVEY OF SYSTEM USERS IN OPD OF CENTRAL SULAWESI PROVINCE) - Monareh, Desya Marcella; Kahar, Abdul (Penelitian dan Pengembangan Ilmu, 2025)
The purpose of this study was to examine and analyze the effect of the quality of human resources in accounting, control activities and the use of information technology on the quality of cooperative financial reports in Central Sulawesi. This study uses a survey research design. The population in this study were all cooperatives operating in Central Sulawesi. The number of cooperatives operating is 59 cooperatives. The method of determining the sample in this study is purposive sampling, namely the sampling is not random and the sample is selected based on considerations or criteria that have been determined. To analyze the hypothesis, the data in this study were processed using quantitative methods with an approach or with the help of PLS ​​(Partial Least Square). The results of the study concluded that the quality of human resources in the accounting field partially has a positive and significant influence on the quality of financial statements. Control activities partially have a positive and significant effect on the quality of financial statements. The partial use of information technology has a positive and significant impact on the optimizing opd performance